2017
DOI: 10.1017/thg.2017.57
|View full text |Cite
|
Sign up to set email alerts
|

Copy Number Variants and Exome Sequencing Analysis in Six Pairs of Chinese Monozygotic Twins Discordant for Congenital Heart Disease

Abstract: Congenital heart disease (CHD) is one of the most common birth defects. More than 200 susceptibility loci have been identified for CHDs, yet a large part of the genetic risk factors remain unexplained. Monozygotic (MZ) twins are thought to be completely genetically identical; however, discordant phenotypes have been found in MZ twins. Recent studies have demonstrated genetic differences between MZ twins. We aimed to test whether copy number variants (CNVs) and/or genetic mutation differences play a role in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 64 publications
2
7
0
Order By: Relevance
“…Nevertheless, the impact of these epigenetic variations on candidate gene expression and thus, their causality for the phenotypic discordance needs to be verified by further studies, in functional respect but also in terms of cases and comparisons (i.e., this study comprises just two cases with each one affected vs. one healthy twin comparison). However, our study confirms other studies on identical twins that discordances in a disease such as CHD cannot be explained by genetic or structural genomic differences [14,[75][76][77][78][79]. Moreover, blood-derived DNA might be chimeric between the identical twins and as shared blood circulations have been found during embryogenesis in most monozygotic twin pregnancies [80], hematopoietic stem cells can be transferred between twins.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Nevertheless, the impact of these epigenetic variations on candidate gene expression and thus, their causality for the phenotypic discordance needs to be verified by further studies, in functional respect but also in terms of cases and comparisons (i.e., this study comprises just two cases with each one affected vs. one healthy twin comparison). However, our study confirms other studies on identical twins that discordances in a disease such as CHD cannot be explained by genetic or structural genomic differences [14,[75][76][77][78][79]. Moreover, blood-derived DNA might be chimeric between the identical twins and as shared blood circulations have been found during embryogenesis in most monozygotic twin pregnancies [80], hematopoietic stem cells can be transferred between twins.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, blood-derived DNA might be chimeric between the identical twins and as shared blood circulations have been found during embryogenesis in most monozygotic twin pregnancies [80], hematopoietic stem cells can be transferred between twins. Such a created hematopoietic system might mask the underlying genetic, structural genomic and also epigenetic differences between the monozygotic twin discordant for a disease like TOF [75].…”
Section: Discussionmentioning
confidence: 99%
“…The copy loss on chromosome 15 has been described in patients with neurodevelopmental defects but not cardiac abnormalities [ 20 ]. The yield of genetic testing in detecting CHD-specific mutations in discordant twins, especially those affected by TTTS, is low, as demonstrated by our negative findings and by studies of copy number variant and exosome sequencing analysis in discordant MC twins [ 4 , 21 ]. On the contrary, genetic tests with high resolution can be diagnostic in concordant pairs, as evidenced by the NOTCH1 gene variant associated with non-syndromic TOF that was seen in the twin pairs with right heart lesion and thumb malformations [ 22 ].…”
Section: Discussionmentioning
confidence: 93%
“…Despite sharing an identical genotype, MC twins can develop discordant phenotypes for congenital malformations including CHD. Studies have not found strong genetic influences on discordant CHD in MC twins, with attributable genetic causes epigenetic in origin as opposed to differences in germline mutations or different phenotypic expression of the same genotype [ 3 , 4 ]. It has been hypothesized that environmental influences such as teratogens can interfere with epigenetic processes leading to differential gene expression and discordant CHD [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Following Xu, Li, et al. (2017), the inclusion criteria for this study were as follows: female sex (due to MRI compliance); MZ twin status; age 28–35 years; right‐handedness; ability to comply with the MRI examination, with no MRI contraindication; no history of substance abuse; for healthy controls, no psychiatric disorder or first‐degree relative with a psychotic disorder; and, for twin pairs, first‐episode schizophrenia with continuous standard treatment in the previous 6 months (≤2 months prior to enrollment) and discontinuation of antipsychotic treatment ≥2 weeks prior to MRI examination in one twin, and no schizophrenia or other psychiatric disorder in the other twin. Healthy control twins were recruited from 26 communities using award‐winning advertisements.…”
Section: Methodsmentioning
confidence: 99%